2003
DOI: 10.7589/0090-3558-39.4.817
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Exposure of White-Tailed Deer (Odocoileus Virginianus) to Mycobacterium Bovis

Abstract: Tuberculosis due to Mycobacterium bovis affects both captive and free-ranging Cervidae in the United States. Various animal models have been developed to study tuberculosis of both humans and animals. Generally, tuberculosis is transmitted by aerosol and oral routes. Models of aerosol exposure of large animals to M. bovis are uncommon. In order to develop a reliable method of aerosol exposure of white-tailed deer (Odocoileus virginianus) to M. bovis, 12 healthy white-tailed deer, aged 8-10 mo, were infected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…17 Moreover, localization of lesions primarily in the lungs and associated lymph nodes has been detected in cattle and white-tailed deer after aerosol exposure to M bovis. 16,18 It is doubtful that aerosol transmission could have played a major role in the study reported here. In the BL-3 building used, air pressure and airflow velocity and direction were monitored continuously to prevent room-to-room transmission of aerosols.…”
Section: Discussionmentioning
confidence: 57%
“…17 Moreover, localization of lesions primarily in the lungs and associated lymph nodes has been detected in cattle and white-tailed deer after aerosol exposure to M bovis. 16,18 It is doubtful that aerosol transmission could have played a major role in the study reported here. In the BL-3 building used, air pressure and airflow velocity and direction were monitored continuously to prevent room-to-room transmission of aerosols.…”
Section: Discussionmentioning
confidence: 57%
“…2 and 3 and Table 1). Cervids have a highly sensitive olfactory system to monitor their environment for predators, prey, food, and/or reproductive cues (18,19), which is also an efficient conduit for airborne pathogens (20,21). The present results demonstrate aerosol transmission of CWD using a dose at least 20 times lower than those in previous oral inoculation studies, yet with infection kinetics equal to or more rapid than oral exposure (2,5,9).…”
mentioning
confidence: 44%
“…M. bovis strain 10-7428 was isolated from a dairy cow in Colorado in 2010. Bacterial inoculums were propagated and prepared as previously described (39). Animals were infected by aerosol inoculation with 10 4 CFU M. bovis 95-1315 (n = 8, experiment 1) or M. bovis 10-7428 (n = 8 in experiment 1, n = 8 in experiment 2) or were mock infected (n = 7 in experiment 1).…”
Section: Animals and M Bovis Challengementioning
confidence: 99%